1997
DOI: 10.1074/jbc.272.23.14611
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Human WW Domain-containing Proteins by Cloning of Ligand Targets

Abstract: A recently described protein module consisting of 35-40 semiconserved residues, termed the WW domain, has been identified in a number of diverse proteins including dystrophin and Yes-associated protein (YAP). Two putative ligands of YAP, termed WBP-1 and WBP-2, have been found previously to contain several short peptide regions consisting of PPPPY residues (PY motif) that mediate binding to the WW domain of YAP. Although the function(s) of the WW domain remain to be elucidated, these observations strongly supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
146
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(150 citation statements)
references
References 50 publications
3
146
1
Order By: Relevance
“…Interestingly, Wiesner et al [38] found that, like Smurf2, deletion of the C2 domain of human WWP2 significantly enhanced its auto-ubiquitination, suggesting that human WWP2 may behave differently from its murine counterpart. Recently, we reported that human WWP2 [46] also targets human OCT4 for ubiquitination and degradation through the 26S proteasome. Unlike Wwp2, WWP2 promotes OCT4 degradation in undifferentiated human ESCs and does not display an inhibition phenomenon at higher dosages.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Wiesner et al [38] found that, like Smurf2, deletion of the C2 domain of human WWP2 significantly enhanced its auto-ubiquitination, suggesting that human WWP2 may behave differently from its murine counterpart. Recently, we reported that human WWP2 [46] also targets human OCT4 for ubiquitination and degradation through the 26S proteasome. Unlike Wwp2, WWP2 promotes OCT4 degradation in undifferentiated human ESCs and does not display an inhibition phenomenon at higher dosages.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility that the antiNedd4 antibody removed WW-domain proteins in addition to Nedd4. The WW-domain-containing proteins (WWPs) identified by Pirozzi et al [30] contain WW domains, bind to Na + -channel peptides and are of a similar predicted molecular mass to Nedd4. However, WW2 of hNedd4 is 82 % identical to rat WW2 (7 amino acid changes out of 38).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have utilized a combinatorial phage display approach to explore the importance of flanking sequences to overall LxxLL motif-receptor interaction [12,13]. This approach is useful given that sequences obtained from this type of screen often reflect sequences found in nature [17,18] and have the potential to act as peptide antagonists for nuclear receptor transactivation [12,13]. In our own previous studies, we have shown that small 19-amino acid (19-mer) LxxLLcontaining peptides originally identified in a phage display screen using purified ERα and ERβ can also bind both VDR and RXR and inhibit vitamin D 3 response [19,20].…”
Section: Affinity Selection Of Ligand-dependent Vdr Binding Peptides mentioning
confidence: 99%